Role of the carbon source in the transformation of amorphous carbon to graphene during rapid thermal processing. Issue 18 (17th April 2019) - Li, Xiaowei; Zhou, Yong; Xu, Xiaowei; Wang, Aiying; Lee, Kwang-Ryeol
Abstract : A fast transfer-free synthesis of a graphene structure can be successfully achieved by Ni-catalysed transformation of amorphous carbon (a-C) during rapid thermal processing, but the role of the a-C structure in the a-C-to-graphene transformation is still unclear. Abstract : A fast transfer-free synthesis of a graphene structure can be successfully achieved by Ni-catalysed transformation of amorphous carbon (a-C) during rapid thermal processing, but the role of the a-C structure in the a-C-to-graphene transformation is still unclear. In this paper, the dependence of the transformation of a-C to graphene, the diffusion behaviour of C, and the graphene quality on the a-C structures was comparatively investigated by reactive molecular dynamics simulation and Ni was selected as a catalyst. The results demonstrated that different a-C structures affected the diffusion of C into Ni layers and the re-dissolving behaviour of the grown graphitic structures, and thus dominated the remnant number of C atoms, which played a critical role in the formation and quality of graphene.